Penerapan Media Ajar Digital Interaktif pada Penulisan Cerpen dalam Mata Pelajaran Bahasa Indonesia di MI Muhammadiyah 02 Pekanbaru - Susanti, Desy (Lembaga Anotero Scientific, 2023)
The application of interactive digital teaching media in learning Indonesian, especially in short story writing material, has the potential to significantly improve student writing skills. This study aims to examine the effectiveness of the use of interactive digital teaching media in improving students' abilities in writing short stories at MI Muhammadiyah 02 Pekanbaru. This study uses a qualitative approach with classroom action research design (CAR) which is carried out in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. Data is collected through observation, interviews, and analysis of the results of students' short stories. The results showed that the use of interactive digital teaching media succeeded in increasing motivation and skills to write students' short stories. Students show developments in the aspects of story ideas, story structure, and the use of more creative and structured language. Digital Teaching Media Interactive, which includes web-based applications with features such as character creation and automatic story lines, providing a more pleasant learning experience and facilitating student creativity exploration. Although there are challenges related to device facilities and student technology skills, the application of this media has a positive impact in creating more effective and interesting learning. This study suggested that the use of digital teaching media be expanded and supported by further training for teachers and students to improve the quality of Indonesian learning